2010
DOI: 10.1126/science.1195846
|View full text |Cite
|
Sign up to set email alerts
|

Response to Comments on “Single-Crystal X-ray Structure of 1,3-Dimethylcyclobutadiene by Confinement in a Crystalline Matrix”

Abstract: Scheschkewitz and Alabugin et al. suggest that photolysis under confinement in a crystalline matrix of 4,6-dimethyl-a-pyrone does not yield the crystal structure of 1,3-dimethylcyclobutadiene (Me 2 CBD) as we reported, but rather that of a 4,6-dimethyl-b-lactone intermediate. We provide arguments that the square-planar Me 2 CBD S /CO 2 complex and the rectangular-bent Me 2 CBD R molecule are stabilized under confinement by the guanidinium-sulfonate-calixarene host matrix used in our study. W e recently reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
0
18
1
1
Order By: Relevance
“…Solid-state photosynthesis of CBD in a crystalline matrix under confined conditions: Inclusion of 4,6-dimethyl-apyrone, Me 2 1, within the G 4 C matrix [17][18][19] in an aqueous solution of either G 4 C/Me 2 1 or 4·G/ C/Me 2 1 components led to single crystals of G 4 CA C H T U N G T R E N N U N G {Me 2 1} (Figure 1).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Solid-state photosynthesis of CBD in a crystalline matrix under confined conditions: Inclusion of 4,6-dimethyl-apyrone, Me 2 1, within the G 4 C matrix [17][18][19] in an aqueous solution of either G 4 C/Me 2 1 or 4·G/ C/Me 2 1 components led to single crystals of G 4 CA C H T U N G T R E N N U N G {Me 2 1} (Figure 1).…”
Section: Resultsmentioning
confidence: 97%
“…All previous studies agree that the CO 2 /CBD interaction results "from the repulsion between CBD and CO 2 rather than an attraction" [4] and is mostly favored by the solid matrix constraints/effects. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Within this context, the 1 H NMR spectra of G 4 CA C H T U N G T R E N N U N G {Me 2 CBD} showed no further evolution after the saturation of the aqueous solution with gaseous CO 2 . These NMR results have been also confirmed by Raman spectroscopy investigations in aqueous solution (see Figure S3 in the Supporting Information for details).…”
Section: Synthesis Of Mementioning
confidence: 89%
See 2 more Smart Citations
“…[12,13] However, this finding initiated heated debate in literature on whether the measured crystal structure corresponds to 1,3-dimethylcyclobutadiene at al. [14][15][16][17] Valence bond isomerism of cyclobutadiene has also aroused considerable interest of theoretical chemists, to mention only the most recent high level computational studies by Balkova and Bartlett, [12] Sancho-Garcia et al, [18] Shen et al, [19] Lefrancois et al, [20] and our research group. [13] We have shown that the barrier for automerization reaction of the parent CBD molecule obtained at the MR-AQCC level of theory including extrapolations to the basis set limit is 6.3 kcal mol −1 .…”
Section: Introductionmentioning
confidence: 99%